Effectiveness of Cardiac Rehabilitation for Patients after Coronary Artery Bypass Graft: Randomized Controlled Trial - Ali Suleiman Harbi; Kim Lam Soh; Putri Yubbu; Kim Geok Soh (Journal of Modern Rehabilitation)
Introduction: Cardiac rehabilitation is a program designed to help patients adopt healthy lifestyle changes. This study aims to investigate the effectiveness of a comprehensive cardiac rehabilitation program (CCRP) on anxiety, depression, perceived health status (PHS) and 90-day readmission rate in patients who underwent coronary artery bypass grafting (CABG). Materials and Methods: A total of 122 patients were randomized into two groups: The intervention group received CCRP. The program lasted for 12 weeks. Anxiety and depression were assessed using the hospital anxiety and depression scale (HADS) and PHS was assessed using the short form-36 health survey. The CCRP’s effectiveness was measured using analysis of variance (ANOVA). Results: The sample comprised 122 participants, of whom 85(69.7%) were male, with a mean age of 53.01±7.26 years. At baseline, the groups showed no significant differences. At 12 weeks and one month later, significant differences were observed between the groups for anxiety (F1=937.69, P<0.001, partial η2=0.90), depression (F1=1036.00, P<0.001, partial η2=0.91), physical component summary (PCS) (F1=14.73, P<0.001, partial η2=0.13) and mental component summary (MCS) (F1=13.87, P<0.001, partial η2=0.121) of PHS, respectively. Conclusion: CCRP is an effective intervention that can significantly improve anxiety, depression, and PHS. Although the readmission rate difference was insignificant, it may have resulted in substantial rewards. The protocol of the present study was registered and approved in ClinicalTrials.gov PRS.